A reappraisal of the problem of submerged deciduous teeth - Freer T.J (Sciendo, 1982)
The etiology of submersence remains unconfirmed although various reasons have been advanced. The condition is generally more prevalent in older children but may be detected as early as 3 years. Treatment has invariably involved extraction. The natural history of the condition involves periods of remission. These remissions and the fact that extractions are not always desirable, led to the treatment of several cases by traction to the affected teeth.